Evaluation of heavy metal availability in contaminated sediments from the Ilha Solteira hydroelectric dam on the parana river at Ilha Solteira, SP, Brazil - Minello, Maria Clara S. [UNESP]; Paçó, Ana L. [UNESP]; Castro, Renata S. D. [UNESP]; Caetano, Laercio [UNESP]; Padilha, Pedro M. [UNESP]; Ferreira, Guilherme [UNESP]; Martines, Marco A. U.; Castro, Gustavo R. [UNESP] (My University, 2010)
This paper investigates the availability of cadmium, copper and lead in surface sediment from a contaminated area in the Ilha Solteira hydroelectric dam. The surface sediment (first 5 cm) was fractionated with plastic sieves and the < 63μm fraction was subjected to a sequential extraction procedure. The pseudototal concentration of metal species, 306.4, 0.092 and 10.1 mg Kg -1 for Cu(II), Cd(II) and Pb(II), respectively, was determined by aqua regia digestion, followed by atomic absorption spectrometry. The results obtained from the sequential extraction procedure indicated that about 10% of Cu(II) and Cd(II) were present in the easily mobilized fraction. All the metal species under investigation showed a predominance of reducible fraction, i.e., more than 50%, while the metal content in the third fraction (oxidizable) varied from 12 to 35%. The metal recovery rate was good, with no significant difference between the amount of metals recovered through the extractant steps and the extractable metals (aqua regia). The results indicate that the sediment poses a risk to aquatic organisms, since a slight change in physical chemical parameters such as pH can mobilize this species to the water column. © by PSP.
Keywords: BCR sequential extraction; Reservoir; Surface sediment; Toxic metals